Transcriptome Analysis of Secondary Metabolism Pathway, Transcription Factors, and Transporters in Response to Methyl Jasmonate in Lycoris aurea - Wang, Rong; Xu, Sheng; Wang, Ning; Xia, Bing; Jiang, Yumei; Wang, Ren (Frontiers in Plant Science, 2017)
Lycoris aurea, a medicinal species of the Amaryllidaceae family, is used in the practice of traditional Chinese medicine because of its broad pharmacological activities of Amaryllidaceae alkaloids. Despite the officinal and economic importance of Lycoris species, the secondary mechanism for this species is relatively deficient. In this study, we attempted to characterize the transcriptome profiling of L. aurea seedlings with the methyl jasmonate (MeJA) treatment to uncover the molecular mechanisms regulating plant secondary metabolite pathway. By using short reads sequencing technology (Illumina), two sequencing cDNA libraries prepared from control (Con) and 100 µM MeJA-treated (MJ100) samples were sequenced. A total of 26,809,842 and 25,874,478 clean reads in the Con and MJ100 libraries, respectively, were obtained and assembled into 59,643 unigenes. Among them, 41,585 (69.72%) unigenes were annotated by basic local alignment search tool similarity searches against public sequence databases. These included 55 Gene Ontology (GO) terms, 128Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways, and 25 Clusters of Orthologous Groups (COG) families. Additionally, 4,175 differentially expressed genes (DEGs; false discovery rate ≤ 0.001 and∣log2 Ratio∣≥ 1) with 2,291 up-regulated and 1,884 down-regulated, were found to be affected significantly under MeJA treatment. Subsequently, the DEGs encoding key enzymes involving in the secondary metabolite biosynthetic pathways, transcription factors, and transporter proteins were also analyzed and summarized. Meanwhile, we confirmed the altered expression levels of the unigenes that encode transporters and transcription factors using quantitative real-time PCR (qRT-PCR). With this transcriptome sequencing, future genetic and genomics studies related to the molecular mechanisms associated with the chemical composition of L. aurea may be improved. Additionally, the genes involved in the enrichment of secondary metabolite biosynthesis-related pathways could enhance the potential applications of L. aurea.